Correlation between Triglyceride/HDL Ratio with Severity of Coronary Artery Lesion in Non-Diabetic Stable Angina Pectoris Patients - Pramon Aditya Sudjana; Chaerul Achmad; Achmad Fauzi Yahya; Januar W. Martha; M. Rizki Akbar (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2018)
Background: Triglycerides (TG) as a risk factor for coronary artery disease (CAD) is still a matter of controversy but when used as a single ratio with high density lipoprotein (HDL) the predictive value for CAD is better. The TG/HDL ratio is also associated with the presence of small dense LDL (sdLDL) in the body. SdLDL is a more atherogenic LDL subfraction and has been proven to be associated with CAD progression.Aims: This study aims to find the correlation between the TG/HDL ratio and the degree of coronary lesion severity based on the Gensini score in stable non diabetic angina pectoris patients.Methods: This study was a cross sectional study conducted at Dr. Hasan Sadikin Hospital and Hasna Medika Palimanan Hospital. Subjects were non diabetic stable angina pectoris patients ≥18 years old who underwent elective coronary angiography. Blood collection for TG and HDL examination was performed after coronary angiography. Gensini scoring system was used to assess the severity of coronary lesions. The relationship between the TG/HDL ratio and the Gensini score was analyzed using multiple linear regression tests against confounding variables.Results: This study involved 60 patients with stable angina pectoris with a mean age of 60±8 years. The mean TG/HDL ratio is 2.56 ± 1.04. The average Gensini score was 51 ± 36. The TG/HDL ratio was significantly associated with the Gensini score (R = 0.637; p <0.001). Analysis of confounding variables showed age, hypertension, and metabolic syndrome had a weak correlation with Gensini score (r values of 0.321, 0.270, and 0.333, p <0.05, respectively), while those correlating with TG/HDL ratios were men, hypertension, and metabolic syndrome (r values of 0.290, 0.287, and 0.362, p <0.05, respectively).Conclusion: TG/HDL ratio was significantly positively correlated significantly with the severity of coronary lesions based on Gensini score in non diabetic stable angina pectoris patients.